Management of Strengthening Islamic Character Education in Senior High School - Nuranifah, Nuranifah; Harun, Cut Zahri; Usman, Nasir (SCAD Independent, 2022)
Islamic character education aims to continuously shape individual self-improvement to train one's ability to lead a life through Islamic guidance. This study aimed to determine: strengthening programs, strengthening implementation, determinant factors in strengthening, and obstacles faced in strengthening Islamic character education at MAN Aceh Besar. This study used a descriptive method with a qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation study. The research subjects were supervisors, school principals, and teachers. The results showed that: (1) The formulated program was incomplete and not detailed, especially regarding using the budget for teacher training activities. The program that was arranged was still implemented as well as possible by the principal to strengthen Islamic character education; (2) The program was implemented by involving all school personnel; (3) The principal followed up on the determinant factor in strengthening Islamic character education is through monitoring activities appropriately every activity that has been programmed; and (4) Obstacle encountered in strengthening Islamic character education include the lack of available funds for teacher training outside of service hours.